2019
DOI: 10.1021/acs.est.9b01112
|View full text |Cite
|
Sign up to set email alerts
|

ClNO2 Production from N2O5 Uptake on Saline Playa Dusts: New Insights into Potential Inland Sources of ClNO2

Abstract: Nitryl chloride (ClNO2), formed when dinitrogen pentoxide (N2O5) reacts with chloride-containing aerosol, photolyzes to produce chlorine radicals that facilitate the formation of tropospheric ozone. ClNO2 has been measured in continental areas; however, the sources of particulate chloride required to form ClNO2 in inland regions remain unclear. Dust emitted from saline playas (e.g., dried lakebeds) contains salts that can potentially form ClNO2 in inland regions. Here, we present the first laboratory measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
88
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(95 citation statements)
references
References 133 publications
7
88
0
Order By: Relevance
“…Aerosol liquid water (or surface‐adsorbed water) largely determines kinetics, mechanisms, and products of heterogeneous reactions (Rubasinghege & Grassian, ; Tang et al, ; Wu et al, ). Mitroo et al () found that at a given RH, N 2 O 5 uptake coefficients decreased whereas ClNO 2 production yield increased with soluble ion fractions in saline mineral dust samples. Furthermore, the dependence of N 2 O 5 uptake coefficients on RH was found to vary with different samples in complicated manners, indicating competing effects between uptake by clay minerals and uptake by soluble contents.…”
Section: Resultsmentioning
confidence: 99%
“…Aerosol liquid water (or surface‐adsorbed water) largely determines kinetics, mechanisms, and products of heterogeneous reactions (Rubasinghege & Grassian, ; Tang et al, ; Wu et al, ). Mitroo et al () found that at a given RH, N 2 O 5 uptake coefficients decreased whereas ClNO 2 production yield increased with soluble ion fractions in saline mineral dust samples. Furthermore, the dependence of N 2 O 5 uptake coefficients on RH was found to vary with different samples in complicated manners, indicating competing effects between uptake by clay minerals and uptake by soluble contents.…”
Section: Resultsmentioning
confidence: 99%
“…Soils in the Lordsburg Playa basin are classi ed primarily as aridisols of the Hondale series (Fine, mixed, superactive, Thermic Natargid) in the Animas Creek delta and along the western shoreline, Playas series (Fine, mixed, superactive, Sodic Haplocambid) in the ephemerally ooded lakebed, and small areas of vertisols of the Verhalen silty clay loam series (Fine, smectitic, thermic Typic Haplotorrerts) on the eastern shoreline. Although the playa surface is saline and alkaline with occasional salt e orescences (puffy growths of evaporite minerals on the surface) (Reynolds et al, 2007), the surface sediments are comprised of primary silicate and clay minerals with lower concentrations of evaporites (salt minerals) than many other dust-emitting playas in North America (Hibbs et al, 2000;Mitroo et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Five months of the year have average maximum temperatures in excess of 30 o C with June, the hottest month, having an average maximum of 35 o C. Soils in the Lordsburg Playa basin are classi ed primarily as aridisols of the Hondale series (Fine, mixed, superactive, Thermic Natargid) in the Animas Creek delta and along the western shoreline, Playas series (Fine, mixed, superactive, Sodic Haplocambid) in the ephemerally ooded lakebed, and small areas of vertisols of the Verhalen silty clay loam series (Fine, smectitic, thermic Typic Haplotorrerts) on the eastern shoreline. Although the playa surface is saline and alkaline with occasional salt e orescences (puffy growths of evaporite minerals on the surface) (Reynolds et al, 2007), the surface sediments are comprised of primary silicate and clay minerals with lower concentrations of evaporites (salt minerals) than many other dust-emitting playas in North America (Hibbs et al, 2000;Mitroo et al, 2019).…”
Section: Methodsmentioning
confidence: 99%